2019
DOI: 10.1002/cctc.201901042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si/Al Ratio on the Catalytic Activity of Two‐Dimensional MFI Nanosheets in Aromatic Alkylation and Alcohol Etherification

Abstract: Zeolite catalysts with pronounced two‐dimensional (2D) morphologies, specifically 2D MFI nanosheets composed of multilamellar stacks of MFI nanosheets, are hypothesized to offer accessibility advantages in catalytic reactions involving large, bulky molecules. The Si/Al ratio of zeolite catalysts is an important parameter determining their performance. However, the effect of Si/Al ratio on catalytic reactivity is not well understood in 2D zeolite catalysts. To provide further insight into this issue, the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(105 reference statements)
1
7
0
Order By: Relevance
“… a Based on refs , ,,,,,, . Abbreviations: n/p–not provided, pm–pore mouth. b Brønsted + Lewis acid sites. …”
Section: Introductionsupporting
confidence: 81%
“… a Based on refs , ,,,,,, . Abbreviations: n/p–not provided, pm–pore mouth. b Brønsted + Lewis acid sites. …”
Section: Introductionsupporting
confidence: 81%
“…Although ethanol dehydration indicates unaltered catalytic activity upon steam treatment, a drastically different outcome is observed when we use benzyl alcohol etherification to dibenzyl ether and benzyl alcohol alkylation with mesitylene as probe reactions under the reaction conditions specified in Section SI in the Supporting Information. The first reaction takes place both in micro‐ and mesopores of SPP, while alkylation can only take place in the mesopores (external surfaces of nanosheets) . In earlier work, we developed a reaction‐diffusion mathematical model (Section SIII in the Supporting Information) for these reactions and obtained the reaction rate and equilibrium constants that determine the observed etherification and alkylation rates .…”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of reactions, including methanol-to-hydrocarbon conversion, ,,, (hydro)­cracking, ,, hydroisomerization, , aromatization, alkylation, ,, C–C coupling reactions, ,,, esterification, ,, acetalization, , etc., have been investigated to assess the catalytic properties of hierarchical zeolites. Many of these studies have reported enhanced catalytic activity for bulky reactants and retarded catalyst deactivation due to suppressed coke formation.…”
Section: Catalysis Using Hierarchical Zeolitesmentioning
confidence: 99%